A multi-time-scale optimization dispatching strategy for the regional DN–MG systems - Sun, Ning; You, Guangzeng; Zhu, Xiaoli; Liu, Yong; Wu, Junhong; Zhu, Huiqiong (Frontiers in Energy Research, 2024)
The optimization dispatching problem of regional distribution network (DN) interconnection with microgrid (MG) is studied in this paper. By installing flexible interconnection devices based on soft open point (SOP) at the boundaries of DNs, the flexible interconnection can be achieved between distribution networks. And the distribution zoning model is established. A multi-objective DN-MG system optimization dispatching model for multi area DNs considering distributed resources is established based on the distribution zoning model. By introducing intermediate coupling variables, the optimization dispatching problem of DN-MG system is decomposed into MG sub area optimization problems and DN sub area optimization problems. On the basis of above, the solution method based on alternating direction method of multipliers (ADMM) is proposed to solve the optimization dispatching model. Finally, simulation verification shows that by application of the proposed method the economic efficiency of the DN-MG system is improved effectively.